A natural indole alkaloid, norharmane, affects PIN expression patterns and compromises root growth in Arabidopsis thaliana - López-González, David (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.